PTU-046 Developing anaesthetist-delivered propofol sedation for advanced endoscopy. (17th June 2017) - Smith, I; Hebbar, S; Lau, K; Durkin, D
Abstract : Introduction: Following recommendations from the Royal College of Anaesthetists (RCA) and British Society of Gastroenterology (BSG) 1 we report our results of propofol sedation for complex endoscopic procedures delivered by a single consultant anaesthetist over a four year period. Method: A service level agreement was used to deliver an average of one session per week to which were scheduled procedures which were complex or could previously not be completed successfully due to inadequate sedation or extreme patient anxiety. Deep sedation was provided by intermittent bolus doses of propofol, supplemented with fentanyl where necessary, titrated to clinical effect. Patients were usually in the semi-prone or lateral position and spontaneously breathed air supplemented with nasal oxygen. Service evaluation included patient recall, endoscopist satisfaction with conditions, procedural success and adverse outcomes. Results: Over four years we completed 811 procedures, 44% of which were for endoscopic retrograde cholangiopancreatography (ERCP) with the remainder comprising a diverse range of endoscopic procedures of 3–156 min duration. These included endoscopic mucosal resection (EMR) polypectomies (54), endoscopic ultrasound (55), oesophageal dilatation (37) and percutaneous endoscopic gastrostomy (PEG) insertion (31). 654 procedures were completed with propofol only while 157 received 25–100 µg fentanyl, mainly due to anticipated post-procedural pain. Procedural conditions were excellent in 80.9% of cases and very good (14.9%) or good in the remainder. 209 procedures were completed which had been previously abandoned, 195 patients (24%) had a better experience than previously and none recalled any part of their procedure. Only 30 procedures were unable to be completed, mostly for technical reasons. Three patients required transient bag and mask ventilation and nasal airways were used in nine patients. Most patients required no airway support, 22.7% required occasional chin support and 4.4% required almost continuous chin support. No patients required tracheal intubation or vasopressor support. Conclusion: These guidelines facilitated a propofol sedation service with considerable benefits for patients and endoscopists. Although established to facilitate ERCP, the service rapidly expanded to meet demands, due to complexity or patient anxiety, of other endoscopic procedures, which ultimately comprised more than half the caseload. Provision of deep propofol sedation by a consultant anaesthetist in patients undergoing endoscopy with an unsecured airway appears practical, effective and efficient. Small adjustments to the airway were fairly common but the incidence of adverse events and requirement for airway instrumentation was low. Reference: . RCA/BSG joint working party. Guidance for the use of propofol sedation for adult patients undergoing ERCP and other complex upper GI endoscopic procedures, 2011. Disclosure of Interest: None Declared